Tinjauan Hambatan Samping Antara SMA Methodist dan SDN 20 Kota Banda Aceh - Bunyamin Bunyamin (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2020)
Pocut Baren Street was a commercial area, and there were several educational facilities where the traffic lane was used every day. In addition, it was also due to the unavailability of parking lots, so many vehicles parked on the roadside and caused traffic jams. The aim was to study and analyze the side barriers to the performance of the Pocut Baren road section between SMA Methodist and SDN 20 Banda Aceh consisting of traffic volume (Q), side barriers (SCF), capacity (C), and degree of saturation (DS). This research was conducted for 3 days, Monday, Friday and Sunday at peak hours in the morning, afternoon and evening starting from 07.00 - 8.00, 08.00 - 09.00, 12.00-13.00, 13.00-14.00, 15.00-16.00 and 17.00 - 18.00 WIB. The method used was Indonesian Road Capacity Manual (MKJI) 1997. The results showed that the level of service on Monday afternoon with Q = 1866.40 pcu / hour, SCF = 591.9 (H), C = 2349 pcu / hour, and DS = 0.79 was in the D category (near unstable currents). Friday morning, Q = 1789.95 pcu / hour, SCF = 511.6 (H), C = 2349 pcu / hour, and DS = 0.76 included in the D category (near unstable current). On Sunday afternoon, Q = 1719.50 pcu / hour, SCF = 466.4 (M), C = 2349 pcu / hour, and DS = 0.73 including the category C (stable current). Side barriers increased very high due to traffic volume if not controlled by The Government immediately.Keywords— Side barriers, capacity, performance of the Pocut Baren road, degree of saturation